THE INFLUENCE OF ENTREPRENEURIAL KNOWLEDGE AND SELF-CONCEPT ON INTEREST IN ENTREPRENEURSHIP - Mahdaly, Zahirah; Marsofiyati; Faslah, Roni (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
This study aims to determine the effect of Entrepreneurship Knowledge (X1) and Self-Concept (X2) with Learning Interest (Y) on Communication Studies Students, Faculty of Social Sciences, State University of Jakarta. This research was conducted for seven months starting from February to September 2021. The research method used was a survey method. The population in this study were 118 respondents. The sampling technique used was simple random sampling technique. Data was collected through a questionnaire with a Likert scale. The data analysis technique used is the multiple regression model. The results of this study have a positive influence between Entrepreneurship Knowledge (X1) and Entrepreneurial Interest (Y). There is also a positive influence between Self-Concept (X2) and Interest in Entrepreneurship (Y). There is a positive influence between the variables of Entrepreneurial Knowledge (X1) and SelfConcept (X2) with Entrepreneurial Interest (Y) simultaneously or together.